2019
DOI: 10.1002/mmce.21831
|View full text |Cite
|
Sign up to set email alerts
|

Low profile four‐port super‐wideband multiple‐input‐multiple‐output antenna with triple band rejection characteristics

Abstract: A quad‐port planar multiple‐input‐multiple‐output (MIMO) antenna possessing super‐wideband (SWB) operational features and triple‐band rejection characteristics is designed. The proposed MIMO configuration consists of four modified‐elliptical‐self‐complementary‐antenna (MESCA) elements, which are excited by tapered co‐planar waveguide (TCPW) feed lines. A radiator‐matched complementary slot is present in the ground conductor patch of each MESCA element. The proposed MIMO antenna exhibits a bandwidth ratio of 36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…These PDAs require a multi-port assistant for smarter connectivity, which is why multi-port antennas are introduced to proliferate its data connectivity in a compact wireless integrated portable system [19][20][21]. Thus, multiple-input-multiple-output (MIMO) proves to be the best solution [22][23][24][25][26][27][28]. For portable handheld smarter devices, usually the dual/tri-port antenna systems are feasible [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…These PDAs require a multi-port assistant for smarter connectivity, which is why multi-port antennas are introduced to proliferate its data connectivity in a compact wireless integrated portable system [19][20][21]. Thus, multiple-input-multiple-output (MIMO) proves to be the best solution [22][23][24][25][26][27][28]. For portable handheld smarter devices, usually the dual/tri-port antenna systems are feasible [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Diversity techniques such as spatial, pattern, and polarization are used to encounter multipath interference. Therefore, a multiple-inputmultiple-output (MIMO)/diversity antenna could be advantageous for vehicular communications [6][7][8][9]. But, the main problem with MIMO antennas is high coupling between resonating elements.…”
Section: Introductionmentioning
confidence: 99%
“…From the available literature, it is observed that the previously reported structures have either large dimensions or bandwidth unable to cover UWB frequency spectrum or beyond it. In the available literature, antenna designers [2433] have used FR-4 epoxy substrate due to its low cost. On the other side, some researchers have avoided it due to its losses at millimeter range frequencies [34, 35].…”
Section: Introductionmentioning
confidence: 99%